Local and international dimensions to credit provision by commercial banks in Kenya - Roseline Nyakerario Misati; Anne Kamau (Kenya Bankers Association (KBA), 2015)
Although considerable research has focused on the determinants of credit to the private sector, the issue still remains controversial, particularly with respect to the role of foreign banks in emerging markets. This study sought to understand the factors that affect lending of commercial bank loans both in form of foreign and local loans. It used panel data methods on quarterly bank-specific data covering the period 2000 to 2013. In general, the results reveal that the ownership structure, housing variable and the size of the bank are the main determinants of aggregate commercial bank lending. This conclusion is maintained even when we specifically examine the determinants of foreign loans and local loans separately. However, the role of the liquidity measure in not consistent in the different specifications while the role of interest rates is largely in line with expectation in most of the specifications. Implicitly, the results seem to suggest a need for mergers of small banks, policy focus on incentives for more local bank ownership and continued efforts on minimization of interest rate spread, which not only promote mortgage financing and home ownership but also overall credit growth.
Keywords: 330